2011
DOI: 10.1021/ma1026719
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Polymer Blends to Cocontinuous Morphology by Asymmetric Diblock Copolymers as the Surfactants

Abstract: We investigated the influence of the chain asymmetry of the styrene (S)Àmethyl methacrylate (MMA) copolymer (surfactant) on the morphology of the polystyrene (PS)/poly(methyl methacrylate) (PMMA) blends. It was, for the first time, demonstrated that the chain asymmetry of the block copolymer surfactant would have significant influence on the structure of the polymer blend in the melt mixing process. In the PS/PMMA = 30/70 blends, the addition of asymmetric AB diblock copolymers tuned the morphology from the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…Fillers and especially nanofillers can change the morphology type and phase size mostly because of a combination of changed viscosity ratios during morphology creation and reduced coalescence due to steric hindrance. Examples of such fillers include nanoclay, carbon black, copolymers, and nanoparticles . For example, Filippone et al have incorporated organoclay into poly(ethylene)/poly (amide) 6 (PA6) blends and found that the clay changes the sea‐island structure of the blends to the cocontinuous morphology, and the rubbery modulus of the composites increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fillers and especially nanofillers can change the morphology type and phase size mostly because of a combination of changed viscosity ratios during morphology creation and reduced coalescence due to steric hindrance. Examples of such fillers include nanoclay, carbon black, copolymers, and nanoparticles . For example, Filippone et al have incorporated organoclay into poly(ethylene)/poly (amide) 6 (PA6) blends and found that the clay changes the sea‐island structure of the blends to the cocontinuous morphology, and the rubbery modulus of the composites increased.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon black and nanoparticles have also been found to change blend morphology. Copolymers and Janus particles can be located at the interface, and can reduce the domain size of the minor polymer phase as well as possibly increasing the interfacial adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Luo et al [47] successfully prepared co-continuous PS/ PMMA blends with only 20 wt% of the minor phase by using asymmetric PS-b-PMMA diblock copolymers as compatibilizers. They assumed that when the longer block of the asymmetric block copolymer was packed on the minor phase side of the interface between the PS and PMMA homopolymers, the bending stress of the copolymer layer could be against the interfacial tension to suppress the breakup of the minor phase fibers during melt mixing, which promoted the formation of the co-continuous morphology.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, understanding the physics of adsorption and desorption of the polymer with one end tethered to a surface is useful to design special surfaces with improved biocompatibility. 1 Surfaces coated with polymers are also relevant to many applications in industrial and biological technologies such as chromatography, 5,6 polymer compatibilization, 7,8 medical implants and bioaffinity sensors. 9 The behavior of polymers near attractive surfaces has been extensively studied in theory and by computer simulation.…”
Section: Introductionmentioning
confidence: 99%